The transformative power of commoning and alternative food networks. Issue 4 (7th June 2019) - Zhang, Joy Y.; Barr, Michael
ABSTRACT: A commoning framework offers a critical lens to fully appreciate the scope and impact of alternative food networks (AFNs). Fieldwork from an AFN in southern China is drawn upon to show how commoning enacts changes in how members contextualise and anchor their social relations to one another with regards to sourcing food as a commons. A commoning framework gives a fuller picture of how the constitutive effects of AFNs reside not in their introduction of a new uniformity but in their navigation of the multiplicity of the social through its proposition and co-construction of a new 'cognitive praxis'.